Systematic investigation of the fatigue performance of a friction stir welded low alloy steel. (5th September 2015) - Toumpis, Athanasios; Galloway, Alexander; Molter, Lars; Polezhayeva, Helena
Graphical abstract: Highlights: The fatigue behaviour of a friction stir welded low alloy steel has been assessed. The welds' fatigue lives outperform the International Institute of Welding's recommendations for fusion welds. The slow weld exhibits the best fatigue performance of the investigated welds. Fracture surface analysis shows that minor embedded flaws do not offer crack initiation sites. Process-related surface breaking flaws have a significant effect on the fatigue life. Abstract: A comprehensive fatigue performance assessment of friction stir welded DH36 steel has been undertaken to address the relevant knowledge gap for this process on low alloy steel. A detailed set of experimental procedures specific to friction stir welding has been put forward, and the consequent study extensively examined the weld microstructure and hardness in support of the tensile and fatigue testing. The effect of varying welding parameters was also investigated. Microstructural observations have been correlated to the weldments' fatigue behaviour. The typical fatigue performance of friction stir welded steel plates has been established, exhibiting fatigue lives well above the weld detail class of the International Institute of Welding even for tests at 90% of yield strength, irrespective of minor instances of surface breaking flaws which have been identified. An understanding of the manner in which these flaws impact on the fatigue performance has been established, concluding that surface breaking irregularities such as these produced by the tool shoulder's features on the weld top surface can be the dominant factor for crack initiation under fatigue loading.